HOUSING RECONSTRUCTION IN A CONFLICT ZONE - LESSONS LEARNED FROM AWARAN, DISTRICT IN BALOCHISTAN, PAKISTAN - Ahmed, Noman (PLANNING MALAYSIA, 2017)
Regions affected by conflict and violence become difficult locations for undertaking routine management and rebuilding. However conditions often arise where input from various stakeholders for relief, rehabilitation and institutional re-vamping become unavoidable. Research and experiences from different contexts inform that outcomes of such interventions have varied results due to unpredictability of contextual conditions, approaches and methodologies adopted for planning and implementations, capacity of personnel involved, available resources and interests of concerned institutions. Awaran district in Balochistan has been impacted by conflict and violence for many years. The impoverished region, apart from social and political turbulence, is recovering from a devastating earthquake that struck the district in September 2013. This paper examines two development interventions in the region; one undertaken by the district administration to streamline the development work through a state sponsored housing reconstruction project and the other by Urban Resource Centre (URC) in collaboration with local communities. Field research for this paper was done during 2014-2015 and comprised review of records, informal discussions with government staff, military officers, community members and working staff of NGOs in the area. After analysing the key findings of these two initiatives, it was found that government sponsored housing reconstruction projects experienced limited success due to usual bureaucratic hurdles and political uncertainties. The community led initiatives were more effective, simple and easy to apply.